State capitalism in a changing global order: Brazil and China’s strategies for greater global influence - Helder Ferreira do Vale; Lilian Costa (Research in Globalization)
This article analyzes the shifts in the global order that occurred in relation to governments' actions and their search for an increased global status within the capitalist global system. Examining the deliberate application of governmental economic interventions, the article examines how Brazil and China leverage state capitalism to enhance their global standing. The comparative analysis of the state capitalist strategy’s implementation in Brazil and China illuminates the various forms of global status seeking and state activism in an evolving global order. By interlinking domestic and international dimensions, the article identifies the elements —preferences, geopolitics, temporality, and state capacity— that have enabled Brazil and China to pursue their global ambitions and augment their global status. The article concludes that Brazil and China adopted the state capitalist strategy; however, the Brazilian strategy was extemporaneous and centralized, whereas the Chinese strategy was planned and multilevel. The primary contribution of the article is to present a framework of analysis that delineates the relevant causes, mechanisms, and contexts for countries in the Global South to influence global politics and economics. Furthermore, the article demonstrates the challenges governments confront in implementing developmental strategies and the importance of rethinking how state activism and international dynamics might benefit Global South countries.